2021
DOI: 10.3390/ani11102783
|View full text |Cite
|
Sign up to set email alerts
|

Potential Novel Biomarkers for Mastitis Diagnosis in Sheep

Abstract: This review aims to characterize promising novel markers of ovine mastitis. Mastitis is considered as one of the primary factors for premature culling in dairy sheep and has noticeable financial, productional, and animal welfare-related implications. Furthermore, clinical, and subclinical mammary infections negatively affect milk yield and alter the milk composition, thereby leading to lowered quality of dairy products. It is, therefore, crucial to control and prevent mastitis through proper diagnosis, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…This study demonstrated a marked increase in APPs (Fb, Cp, SAA, and Hp) concentrations in CMG. Similar observations were reported before for mastitis in camels and other animal species [ 15 , 19 21 ]. Additionally, the pro-inflammatory cytokines prompt free radicals liberation from different immune cells.…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrated a marked increase in APPs (Fb, Cp, SAA, and Hp) concentrations in CMG. Similar observations were reported before for mastitis in camels and other animal species [ 15 , 19 21 ]. Additionally, the pro-inflammatory cytokines prompt free radicals liberation from different immune cells.…”
Section: Discussionsupporting
confidence: 90%
“…Veillonella parvula is not able to ferment carbohydrates and lives on the lactate produced by Streptococci [ 81 , 82 ], so it is reasonable to assume that this bacterium was rather isolated due to the isolation of the aforementioned Streptococci. Finally, the two Enterobacteriaceae species ( Enterobacter cloacae and Enterobacter kobei ), although pathogenic for the respiratory tract, are considered major pathogens for the mammary gland [ 83 , 84 ]. All these findings suggest a semi-protective effect of the dietary omega-3 fatty acids on bacterial populations in the udder.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of these proteins, determined in the last phase of pregnancy and after calving, may relate to the changing hormone profile (the influence of oestrogens and progesterone) [ 10 , 20 ]. The physiological role of SAA is the inhibition of lymphocyte proliferation, oxidative reactions in neutrophils, and platelet and thrombocyte aggregation and detoxification of endotoxins [ 29 ]. Fibrinogen binds specifically to the CD11/CD18 receptors on the migrated phagocytes’ surface and releases a cascade of intracellular signals that lead to increased phagocytosis, degranulation, and antibody-dependent cellular cytotoxicity and apoptosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%